The Postmodern condition: A report on knowledge - Lyotard, Jean-François 1924-1998 (Manchester Manchester University Press, 1986)
Many definitions of postmodernism focus on its nature as the aftermath of the modern industrial age when technology developed. This book extends that analysis to postmodernism by looking at the status of science, technology, and the arts, the significance of technocracy, and the way the flow of information is controlled in the Western world.